The Impact of Trade Liberalization on Income Inequality in Developing Economies - Septa Atmoko Purmanajati; Muhammad Bagas Saputra; Dwiki Fadli Ade Novianto (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This article investigates the relationship between trade liberalization and income inequality in developing economies. Using empirical data from a range of countries that have undergone significant trade policy reforms, the study examines how opening markets to global trade influences income distribution. It finds that while trade liberalization often leads to overall economic growth, it can also exacerbate income inequality within countries. The paper argues that the design of trade policies should account for redistributive mechanisms to mitigate the adverse effects on vulnerable populations.